Preparation And Characterization Of Poly(Butylene Adipate-Co-Terephthalate)/Poly(Vinyl Chloride)/Clay Nanocomposites - Mohd Rahim, Mohd Nazri (2010)

(untitled)
This research focused on blending poly(butylene adipate-co-terephthalate) (PBAT) with poly(vinyl chloride) (PVC) and effect of organoclay on the properties of PBAT/PVC composites. In order to improve the clay and polymer compatibility, the clay was first converted into the organoclay. The organo-montmorillonite (OMMT) was prepared via ion exchange technique using organic surfactants; octadecylamine (ODA) and dimethyldioctadecyl ammonium bromide (DDOAB). The X-ray Diffraction (XRD) results revealed that the interlayer distance of the sodium montmorillonite (Na-MMT) increases with the formation of the organoclays. The presence and the amount of the alkyl ammonium ions in the organoclays were also characterized using Fourier Transform Infrared spectroscopy (FTIR) and Thermogravimetric Analysis (TGA), respectively.